Synthesis and Characterization of Chalcone Derived Heterocyclic Compounds and Their Biological Activities - Saba, Farooq (Universiti Malaysia Sarawak (UNIMAS), 2021)
The antibiotic resistivity of drugs has become one of the major clinical problems that cause complications, morbidity and mortality along with infection. To overcome the health crisis, new potent drugs are still in demand in the medicinal industry. A series of carboxyl chalcone derivatives (47a-m and 54a-j) were successfully synthesized via Claisen-Schmidt condensation, followed by cyclization into pyrazoline derivatives such as acetyl pyrazoline (49a-k and 55a-j), phenyl pyrazoline (50a-k and 56a-j) via Aza-Michael addition reaction. The carboxyl pyrazolines were esterified to form the 53a-g and 57a-g through the Fischer esterification reaction. All synthesized compounds were analysed using elemental analysis Carbon, Hydrogen and Nitrogen (CHN) and characterised via Fourier Transform Infrared Spectroscopy (FTIR), 1H and 13C Nuclear Magnetic Resonance (NMR) spectroscopy. The antimicrobial activities of the synthesized compounds were evaluated via turbidimetric kinetics and disc diffusion assay against Escherichia coli (ATCC25922) and Staphylococcus aureus (N5923). Antimicrobial studies of chalcone series 47a-g and 54a-c revealed moderate activities with inhibition zone 5-13 mm against S. aureus, where 47b and 47e depicted the highest inhibition zone (13 mm and 12 mm) compared to the ampicillin (11 mm). The phenyl pyrazoline derivatives 50a-k and 56a-j showed excellent inhibition zone 11-19 mm against S. aureus due to the presence of -N-N-, COOH, and halogens in the heteroaromatic compounds. The presence of fluorine in 52b depicted the highest zone of inhibition (19 mm). The acetyl series (49a-k and 55a-j) and esterified series (53a-g and 57a-g) depicted no inhibition zone in all compounds. The structure-activity relationship (SAR) of selected compounds was evaluated via molecular docking using AutoDock Vina. The molecular docking studies against S. aureus protein 4pql depicted good binding affinity of -6.6 kcal/mol -7.1 kcal/mol compared to ampicillin drug (-6.6 kcal/mol). This research accomplished with strong antimicrobial activities of heterocyclic pyrazolines compared to chalcones, which will be advantageous for the pharmaceutical industry in new drug production.